Author correction: the copy number variation landscape of congenital anomalies of the kidney and urinary tract - Verbitsky, Miguel; Lozanovski, Vladimir J. (Nature genetics, 2019)
In the version of this article initially published, affiliation 38 incorrectly read “ICNU-Nephrology and Urology Department, Barcelona, Spain”; “Renal Division, Hospital Clinic, IDIBAPS, University of Barcelona, Barcelona, Spain” is the correct affiliation. The error has been corrected in the HTML and PDF versions of the article.